ANALYSIS OF REGIONAL REVENUE AND EXPENDITURE BUDGET OF MAGELANG REGENCY - Triane Vera Utami; Erni Puji Astutik (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This research aims to describe the targets and realization of the Regional Revenue & Expenditure Budget in the Magelang Regency Government. Research using a qualitative narrative approach was chosen in this essay to state the targets and realization of the Magelang Regency Government's Regional Revenue & Expenditure Budget. The results of the research on targets & realization of the Regional Revenue & Expenditure Budget (APBD) of Magelang Regency for the period 2016 to 2018 show that Magelang Regency's regional income has not been relatively good & effective in realizing its income. The level of realization of spending in the Magelang Regency Government has started relatively well in realizing it.